2007
DOI: 10.1159/000101915
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of the Effectiveness of Acidic Fluoride Dentifrices

Abstract: This study evaluated the effectiveness of acidic low-fluoride dentifrices compared to conventional neutral dentifrices. Enamel blocks were submitted to pH cycling and treatment with slurries of dentifrices containing 0, 275, 412, 550 and 1,100 µg F/g (pH 4.5 or 7.0), and also a commercial dentifrice (1,100 µg F/g) and a commercial children’s dentifrice (500 µg F/g). Variations in surface microhardness and in the mineral content in enamel after pH cycling were calculated. Enamel blocks treated with acidic denti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 24 publications
0
58
2
3
Order By: Relevance
“…Based on this philosophy and aiming to minimize the ingestion of fluoride by young children in order to prevent dental fluorosis, toothpaste with a low concentration of fluoride has been developed. 27 Several studies have shown that low-fluoride toothpastes do not present statistically significant differences in terms of their effect when compared with conventional toothpastes, and in addition to ensuring the same effectiveness, they also offer greater safety in terms of fluorosis. 23,27 However, the effect of these toothpastes has not yet been compared with that of silver diamine fluoride, fluoride varnish and fluoride gel.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this philosophy and aiming to minimize the ingestion of fluoride by young children in order to prevent dental fluorosis, toothpaste with a low concentration of fluoride has been developed. 27 Several studies have shown that low-fluoride toothpastes do not present statistically significant differences in terms of their effect when compared with conventional toothpastes, and in addition to ensuring the same effectiveness, they also offer greater safety in terms of fluorosis. 23,27 However, the effect of these toothpastes has not yet been compared with that of silver diamine fluoride, fluoride varnish and fluoride gel.…”
Section: Groupmentioning
confidence: 99%
“…27 Several studies have shown that low-fluoride toothpastes do not present statistically significant differences in terms of their effect when compared with conventional toothpastes, and in addition to ensuring the same effectiveness, they also offer greater safety in terms of fluorosis. 23,27 However, the effect of these toothpastes has not yet been compared with that of silver diamine fluoride, fluoride varnish and fluoride gel. From that standpoint, therefore, the present study used toothpaste containing a low concentration of fluoride (500 ppm F).…”
Section: Groupmentioning
confidence: 99%
“…Among the in vitro models used worldwide, pH cycling simulates caries development under controlled condi- tions [White, 1995] and gives information on surface and subsurface enamel in caries dynamics [ten Cate and Mundorff-Shrestha, 1995]. The pH cycling model of Vieira et al [2005] for bovine teeth, based on the studies of ten Cate and Duijsters [1982] and Featherstone et al [1986], is a sensitive methodology for verifying the fluoride dentifrice dose-response relationship [Brighenti et al, 2006;Alves et al, 2007;Takeshita et al, 2009]. As a short-term pH cycling model, it provides a lower demineralization and a surface layer and lesion depth considered 'small'.…”
Section: Discussionmentioning
confidence: 99%
“…The tubes were agitated for 30 minutes, then 0.8 mL NaOH 0.5 mol/L was added. 15 Fluoride measurements were performed with an ion-selective electrode (Orion 9609-BN, Orion Research, Inc, Beverly, MA, USA) and a digital ion analyzer …”
Section: Analysis Of Fluoride In Enamel and Ph-cycling Solutionsmentioning
confidence: 99%